Radiological picture of ophthalmic syndrome - Babić, Rade; Stanković-Babić, Gordana; Govedarović, Nenad; Babić, Strahinja; Marjanović, Aleksandra; Babić, Nevena (Medical Word, 2020)
It’s common for the syndromes indicate to the author or authors who discovered them. The paper aims to show the image of X-rays and ophthalmic ophthalmic syndrome and to point out to those who can be recognized by the proper radiological and ophthalmologic examination. The work is based on knowledge and experience of the author and co-author of the acquired long experience in the profession, acquired many years of ophthalmology and radiological material, the papers presented in the relevant national and international journals, history and local and foreign literary press. Are shown in - Syndrom Stuger-Weber-Krabbe, Syndrome Wyburn-Mason, Syndrome Von Hippel-Lindau, Syndrome Crouzon, Syndrome Apertand Syndrome Saethre-Chotzen. The authors conclude that ophthalmic syndromes have their own specificity in radiologically-ophthalmologic image.
Keywords: syndrome, radiology, ophthalmology